SiC nanoparticles additions to squeeze-cast Mg-5.0Al-2.0Ca-0.3Mn alloy: An evaluation of microstructure and mechanical properties - Nasker P.; Mondal A.K. (My University, 2025)
The influences of the SiC nanoparticles (SiCnp) content on the microstructural modification and mechanical properties of the squeeze-cast Mg-5.0Al-2.0Ca-0.3Mn (AXM520) alloy have been investigated. The concentrations of the SiCnp are varied from 0.5 to 3.0 (wt%), and the nanocomposites (NCs) are abbreviated as NC0.5SiC, NC1.0SiC, NC2.0SiC and NC3.0SiC. The as-cast microstructures of the AXM520 alloy and NCs consist of an α-Mg phase, a eutectic of α-Mg and (Mg,Al)2Ca (C36), and an Al8Mn5 phase. Additionally, the SiC phase is also present in the NCs. The continuous network of the C36 phase is fragmented and becomes discontinuous as the content of the SiCnp increases in the NCs. All the NCs exhibit superior tensile and compressive properties than the AXM520 alloy. The NC2.0SiC exhibits the best tensile properties among the NCs employed. The YS of the NCs improves with the increase in the SiCnp content up to 3.0 (wt%). The UTS and %El of the NCs increase up to 2.0SiCnp (wt%), and beyond that, the same declines owing to the agglomeration of the nanoparticles. The discontinuous network of the C36 phase in the NCs inhibits crack propagation, leading to their improved %El. All the NCs exhibit higher strain-hardening exponent (n) and strain-hardening rate (SHR) compared to the AXM520 alloy. The superior ‘n’ and SHR exhibited by the NCs were attributed to the grain refinement and dislocations generation. The strengthening from CTE mismatch contributes the most to the overall strengthening of the NCs. The ‘Zhang and Chen’ model is modified by introducing an agglomeration factor, and the predicted YS of the NCs matches pretty well with the experimentally obtained values. © 2023